Penghayatan Panggilan Karier (Vocational Calling) pada Dewasa Awal dalam Transisi Karier Menjadi Guru melalui Program Pendidikan Profesi Guru (PPG): Studi IPA pada Peserta PPG - Rahma Sari Putri Tambunan; Nuraisah Rizki Syahputri; Masril Masril (Scidacplus, 2026)
The phenomenon of career transition to the teaching profession through the Teacher Professional Education Program (PPG) is increasingly found among young adults who previously worked in non-educational sectors. This phenomenon is interesting to study because the decision is not always based on economic considerations, but is often related to the search for work meaning and the appreciation of vocational calling. This study aims to understand in depth the process of vocational calling in young adults who choose to transition to teaching through the PPG program. The study used a qualitative approach with an Interpretative Phenomenological Analysis (IPA) design. The study participants were 4 (four) early adults aged 23–35 who were currently attending PPG at the University of Muhammadiyah North Sumatra and had at least one year of work experience outside the teaching profession. Data were collected through in-depth semi-structured interviews and analyzed using phenomenological procedures, including bracketing, horizontalization, theme grouping, and synthesis of the meaning of experiences. The research results identified five main themes, namely (1) existential dissonance in previous jobs, (2) critical moments as triggers for career transitions, (3) calling from external-transcendental sources, (4) reorientation of professional identity, and (5) the meaning of the teaching profession as a social contribution and self-actualization. The findings indicate that vocational calling develops as a dynamic psychological process through interactions among value incongruence with previous jobs, meaningful reflective experiences, social support, and the reconstruction of professional identity during PPG. This research broadens the understanding of vocational calling in the context of career transitions. It provides implications for career counseling services in helping individuals find jobs that align with their identity, values, and life goals.